Home Language and Literacy Pedagogy: Addressing the Foundational Learning Needs of Tribal Children in Multilingual Classrooms of Chhattisgarh - Bagwan, Sunil Kumar (International Journal of Learning and Instruction (IJLI), 2025)
This research investigates the pedagogical role of home languages in foundational literacy instruction among tribal children in multilingual classrooms of Chhattisgarh. Grounded in the framework of the National Education Policy (NEP) 2020 and the National Curriculum Framework for the Foundational Stage (NCF-FS) 2022, the study explores how local languages such as Chhattisgarhi, Gondi, and Halbi can be effectively utilized in early-grade classrooms to promote culturally responsive and meaningful learning. Through classroom observations and policy analysis, the paper highlights how bilingual and multilingual teaching practices, supported by contextually developed materials, help overcome language barriers and contribute to literacy acquisition and cultural identity formation. The study underscores the necessity for professional development of teachers, the development of local language resources, and instructional strategies that respect linguistic diversity. It further advocates for a policy shift towards inclusive language-based pedagogies that support both cognitive development and heritage preservation in tribal-dominated regions.